STUDY OF THE EFFECT OF THE USE OF ADDITIONAL ADDITIVES DAMDEX AND BESTMITTEL ON THE COMPRESSIVE STRENGTH OF CONCRETE f'c 20 MPa. - Dina Heldita (Journal of Green Science and Technology, 2021)
Under normal circumstances, the maximum strength of the concrete will be reached at the age of 28 days, but to achieve the initial maximum strength of the concrete can be done in 2 ways, namely the use of Portland cement or the use of mineral additives or chemical admixtures. Another purpose of the use of admixture is the fulfillment of a short concrete execution time but the performance of the concrete is maintained.This study aims to determine the comparison of the compressive strength (N/mm2 unit) of normal concrete with concrete that uses Damdex and Bestmittel added materials, the test object used is cylindrical with the percentage addition of Damdex 2% and Bestmittel 0.2% of the weight of cement with composition the mixture used using the Job Mix Formula f'c 20 MPa for the Block B/F Heavy Rehab work project, Kotabaru District Prosperity Market Complex, namely for 1 m3 using 442.00 kg of cement, 681.79 kg of fine aggregate, 1065.72 kg of coarse aggregate , 215 liters of water. With the age of the tested concrete the compressive strength is 14 and 28 days.The results of the normal concrete compressive strength test at 14 and 28 days on average were 20.33 MPa and 22.19 MPa from the design compressive strength (f'c) of 20 MPa. Meanwhile, for the mixture with 2% Damdex and Bestmittel 0.2% added materials at 14 and 28 days the average was 22.93 MPa and 20.76 MPa from the design compressive strength (f'c) 20 MPa..Keywords: Concrete Quality, Damdex, Bestmittel, Compressive Strength